(untitled) (Journal of the College of Education for Women, 2019)
AbstractLanguage is one of God’s blessings to human beings through which hedistingushed them from other creatures, then how if this language was arabic.God honored this language and in which he descended his Gracious Boolethat gave it glory and magnificance, and made it an immortal revelation to thearab nation in their poetry, oration, history and human tendency to the life ofknowledge, mind leadershipe, innovation and progress.This study aimed at evaluating the arabic language come program forthe new teachers. The sample was of (25) participants who were shown aquestionaire consisting of (60) items distributed on (9) fields. Then, the datawas processed statisically by using preauency rate, Kai square andpercentage weight. The study reached into ahumber of results, conclusionsand recommendations